Increased reproductive trait diversity, evolutionary history and distinctiveness during the succession of tropical forest. (19th November 2021) - Romanowski, Luciele Leonhardt; Zanata, Thais Bastos; Marques, Marcia C. M.; Carlucci, Marcos Bergmann; Varassin, Isabela Galarda
Abstract: Questions: Do old‐growth forests retain more evolutionary history and more reproductive trait diversity along the successional gradient? How similar are the phylogenetic branches and reproductive attributes at each phase? In which succession stages are distinct lineages of trees and shrubs present? Do distinct lineages have distinct traits? Is there a turnover of species, lineages and traits of trees and shrubs along the successional gradient? Location: Atlantic Forest, Reserva Natural Guaricica (25°19′ S, 45°42′ W) and Reserva Natural das Águas (25°21′ S, 48°46′ W), Antonina, Paraná, southern Brazil. Methods: We assessed the variation of alpha and beta taxonomic, functional and phylogenetic diversities of tree and shrub communities along a successional gradient (phase 1, stand initiation phase, from 0 to 9 years old; phase 2, stem exclusion phase, 10–25 years old; and phase 3, understorey re‐initiation phase, 25–200 years old). We also evaluated the occurrence of distinct lineages and traits related to seed dispersal and pollination. Results: In addition to the expected change in species composition, lineages and trait states and values were replaced along the chronosequence, with stronger variation for trees. Old‐growth forests harbor distinct lineages and traits and a greater amount of evolutionary history and functional diversity of reproductive traits. We also found that distinct lineages were those that performed distinct functions. Conclusions: Our study showed that as the succession proceeds, turnover of lineages and traits occurred, with the understorey re‐initiation stage harboring the largest taxonomic, phylogenetic and functional diversity. In addition, understories of the re‐initiation stage are important for the occurrence of distinct lineages, such as magnoliids, and of distinct traits, such as large fruits and seeds, which highlights the importance of conservation of old‐growth forests, and its preservation can prevent the loss of distinct evolutionary histories and functions. Abstract : What happens to tropical forests when they get old? Older forests have more species, a larger amount of evolutionary history, and more diverse reproductive traits. They are also unique in terms of plant evolutive lineages and reproductive traits. Our study highlights the importance of conserving older forests since along with their loss, distinct evolutionary histories and distinct functions are lost.